A New Stability of the S-Essential Spectrum of Multivalued Linear Operators - Aymen Ammar; Slim Fakhfakh; Aref Jeribi (International Journal of Analysis and Applications, 2017)
We unfold in this paper two main results. In the first, we give the necessary assumptions for three linear relations $A$, $B$ and $S$ such that $σ_{eap,S}(A+B)= σ _{eap,S}(A)$ and $σ_{eδ,S}(A+B)= σ_{eδ,S}(A)$ is true. In the second, considering the fact that the linear relations $A$, $B$ and $S$ are not precompact or relatively precompact, we can show that $σ_{eap,S}(A+B)= σ_{eap,S}(A)$ is true.